P237 Age at menopause and lung function: a mendelian randomization study. (December 2018) - van der Plaat, DA; Pereira, M; Pesce, G; Potts, J; Amaral, A; Dharmag, S; Garcia-Aymerich, J; Gómez-Real, F; Jarvis, D; Minelli, C; Leynaert, B
Abstract : Epidemiological studies suggest menopause, especially at an early age, is associated with lower lung function. This association may be causal or could be explained by residual confounding (e.g. smoking). We used a Mendelian randomization (MR) approach, which is not affected by classical confounding, to assess the causal effect of age at menopause on lung function. Using UK Biobank data of 94 742 naturally post-menopausal women (age 41–71), we performed MR analyses on the effect of age at menopause on lung function (FVC, FEV1, FEV1 /FVC), restriction (FVC <LLN), and obstruction (FEV1 /FVC <LLN). MR was performed using 63 independent SNPs identified by previous GWA studies as proxies for age at menopause. We used the inverse variance-weighted (IVW) method and we investigated and adjusted for pleiotropy. We compared the MR results to observational results from linear/logistic models adjusted for confounders. In contrast to the observational findings of higher FEV1 and FVC, and slightly higher FEV1 /FVC ratio, associated with increased age at menopause, the MR analysis showed statistically lower FEV1 and FEV1 /FVC and a higher risk of obstruction, with no effect on FVC or restriction (figure 1). Women with early menopause (<45 years) had a 15% reduction in the risk of obstruction (OR 0.85 [0.82–0.89]). Although there was heterogeneity in MR estimates across SNPs suggesting pleiotropy (I 2 17 to 53), using MR methods robust to pleiotropy (random-effect IVW, weighted median, MR Egger) showed highly consistent findings for FEV1 /FVC and FEV1 /FVC <LLN (figure B/E) and supported no association with FVC. Subgroup MR analyses did not show a difference in the effect on obstruction between never- and ever-smokers, while the detrimental effect of increasing age at menopause was less strong in menopause hormone treatment (MHT) users and in women with a BMI≥26. Our MR analyses suggest that early menopause has a protective effect on airway obstruction, contradicting observational findings. This might be explained by shorter exposure to female sex hormones, specifically estrogens, which seems to support previous research in mice showing that estrogens may contribute to airway remodeling. (ALEC, EU Grant #633212).